2020
DOI: 10.3390/ani10050757
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrolysable Tannins as Zinc Oxide Substitutes on Antioxidant Status, Immune Function, Intestinal Morphology, and Digestive Enzyme Activities in Weaned Piglets

Abstract: Zinc oxide (ZnO) has negative environmental effects and bioavailability in weaned piglets. Thus, finding safe and effective ZnO substitutes to improve intestinal health and to prevent diarrhea of weaned piglets is urgently required. Therefore, this experiment was conducted to evaluate the effects of hydrolysable tannins (HT), ZnO and HT versus ZnO on growth performance, antioxidant status, serum immunity, intestinal morphology, and digestive enzyme activities in weaned pigs. A total of 144 piglets (28 d-old, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 43 publications
4
46
0
Order By: Relevance
“…With the exception of some members of the phenolics family (tannins, saponons, toxic alkaloids) the most of the plant extract did not show anti-nutritive in animal diets [ 4 ]. For example, high concentration of condensed tannins from certain plant extract in animal feed can precipitate protein digestion showed lower performance with nutrient retention in monogastric animals [ 5 , 6 ]; whereas higher body weight with improve health status in chickens offered hydrolysable tannins was recorded [ 7 ]. This is because hydrolysable tannic acid extracted from wood was enrich with polyphenolic compounds [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of some members of the phenolics family (tannins, saponons, toxic alkaloids) the most of the plant extract did not show anti-nutritive in animal diets [ 4 ]. For example, high concentration of condensed tannins from certain plant extract in animal feed can precipitate protein digestion showed lower performance with nutrient retention in monogastric animals [ 5 , 6 ]; whereas higher body weight with improve health status in chickens offered hydrolysable tannins was recorded [ 7 ]. This is because hydrolysable tannic acid extracted from wood was enrich with polyphenolic compounds [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The perception of applying natural polyphenols in poultry and swine diets has been tested since 1989 [ 27 ] and later on it was considered for further research during the last two decades due to their potential biological roles [ 6 , 28 ]. The biological role of phenolic compounds with their mode of action in farm animals were described in details below.…”
Section: Introductionmentioning
confidence: 99%
“…Tannins are secondary plant metabolites that are commonly classified under 2 groups, condensed tannins and hydrolysable tannins. Condensed tannins hold the antinutritional factors and could decrease protein digestibility because of its protein precipitation nature, and thus, the long-term uses of condensed tannins could decrease the growth performance and nutrient digestibility in monogastric animals ( Smulikowska et al., 2001 ; Liu et al., 2020 ). On the other hand, it is believed that hydrolysable tannins have a positive role in growth performance and health status in chickens ( Schiavone et al., 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…colonization. Hosseindoust et al [24] and Liu et al [7] reported that the antimicrobial activity of ZnO against coliforms makes it an ideal candidate to control the microbiota, however, they did not report any change in the number of Clostridium spp. In another study, the population of coliforms and Clostridium spp.…”
Section: Discussionmentioning
confidence: 98%
“…There is evidence that high doses of dietary ZnO controlled pathogen growth in the intestine [6]. Besides, dietary supplementation with high doses of ZnO increases the absorption rate that can enhance the antioxidant status [7]. However, feeding high doses of ZnO results in substantial quantities of Zn excretion, and causes environmental concerns [6].…”
Section: Introductionmentioning
confidence: 99%